Recycling of automotive catalytic converters with application of magneto-hydrodynamic pump - Wójcik, Marta; Pawłowska, Beata; Stachowicz, Feliks (Advances in Mechanical and Materials Engineering, 2016)
The automotive catalytic converter is a part of exhaust system in vehicles, which reduces the amount of harmful substances in exhaust fumes. The need of using automotive catalytic converters results from rigorous standards for exhaust fumes emissions, called EURO standards. In Poland, there is not any installation designed in order to recycle worn out automotive catalytic converters. Catalytic converters are purchased by individual entrepreneurs and exported abroad. This article presents a solution of recycling of catalytic converters which can recover precious metals contained in catalytic converters. This article also characterizes automotive catalytic converters and reviews the standards of exhaust fumes emission.